Faktor-Faktor Penyebab Turunnya Dominasi Partai Akp Dalam Pemilu Legislatif Turki Tahun 2015 - Frederikus Nong Wair; Harmiyati Harmiyati (Jurnal Paradigma, 2015)
Present Turkey political situation indicates instability since the promulgation of Turkey legislative general election 2015 in which breaking AKP party domination in attaining votes of most electors since it has participates in Turkey political area in 2001. The interesting matter is that AKP is the only one party founded by Islamic gures that can ght in Turkey politic for more than one decade since the Republic system triggered by Mustafa Kemal Ataturk in 1923 and the multi parties system has been implemented since 1940s. It should be noted that Islamic political parties often face intervention both from government and military in which it forces them to be dissolved, even more tragically their administration is carried out a coup d’etat by military after those Islamic parties obtained victory and build their administration as welfare party built by Mohammad Erbakan. The wisdom is drawn from bitter experiences faced by this Islamic Party and become reference in formulating, shaping and running more polite polici towards Turkey Arbiter and administration institution known as “secularism” watchman, by their young gures which are incorporated in a party known as Adelet ve Kalkinma Partisi (AKP). The courageous and dignity of AKB for 13 years on Turkey administration through the main actor, Racep Tayyib Erdogan that suddenly must collapse after the result of Turkey legislative general election 2015 is promulgated. Although during this party dominance has showed very excellent achievement in various life aspects, it can’t be a guarantee for AKB and Erdogan to continue its dominance as a single dominant party in Turkey. It becomes very crucial with Turkey constitution system change discourse that will be changed by Erdogan from parlementary to presidential with a prerequisite such as the majority victory of the general election. This dream must nally be “postponed” for a certain period which is dif cult to determine because of the reality. It is important to note about factors cause them occur are. Therefore, this paper will discuss AKB and the cause of this party dominance reduces.